The importance of Asn52 in the structure–function relationship of human cytochrome c. Issue 73 (18th December 2020) - Lou, Dan; Liu, Xi-Chun; Wang, Xiao-Juan; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu
Abstract : Naturally occurring N52S human cytochrome c adopts a small fraction of high-spin species and exhibits an enhanced peroxidase activity. Abstract : The function of the highly conserved residue Asn52 in human cytochrome c (H-Cyt c ) is not fully understood. Herein, we show that the naturally occurring variant N52S H-Cyt c has a perturbed secondary structure, with a small fraction of high-spin species. Remarkably, it exhibits an enhanced peroxidase activity by 3–8-fold at neutral pH, as well as self-oxidation in reaction with H2 O2 . This study suggests that the H-bond network mediated by Asn52 is essential to suppress the apoptotic activity of H-Cyt c under physiological conditions.